Growth hormone utilization review in a pediatric primary care setting - Fatemeh Sayarifard; Fereshteh Bakhshi Imcheh; Shirinsadat Badri; Toktam Faghihi; Mostafa Qorbani; Mania Radfar (Wolters Kluwer Medknow Publications, 2017)
Objective: One of the main problems facing public health providers and administrators in many countries is ensuring the rational use of high-cost drugs. In this regard, on-going process of medication use evaluation can be considered as a useful tool. In this study, we evaluated certain usage aspects of a highly-cost medication, that is, recombinant growth hormone (GH). Methods: This cross-sectional study conducted from August 2012 to August 2014. Children receiving GH ± gonadotropin releasing hormone (GnRH) analogs were included in the study. A researcher-designed checklist was developed to evaluate the GH utilization in these patients. Baseline demographic characteristics and background clinical and growth data, as well as any aspects of drug therapy including indications, dosing, monitoring, and discontinuation were collected from the patients' medical records. Findings: Seventy children receiving GH entered the study, of which 23 patients (32.85%) received GH and GnRH analogs simultaneously. At the baseline, 67 children (95.7%) had GH stimulation test, whereas serum insulin-like growth factor-1 (IGF-1) levels were measured in 63 (90%) patients. Sixty-seven patients (95.71%) had thyroid function test, whereas bone age was determined in 68 children (97.14%). The mean ± standard deviation of GH dose for idiopathic short stature, GH deficiency, Turner's syndrome and born small for gestational age in our study was 0.22 ± 0.025 mg/kg/week, 0.23 ± 0.04 mg/kg/week, 0.22 ± 0.015 mg/kg/week, and 0.23 ± 0.02 mg/kg/week, respectively. Height and weight of all patients were followed every 3-6 months, regularly. Thirty patients were treated with GH for at least 1 year, of which thyroid hormones and IGF-1 levels were measured annually in 25 (83.33%) and 26 (86.66%) patients, respectively; while bone age was evaluated in 13 (43.33%) children, annually. GH treatment was discontinued in 15 patients (21.42%), while financial problem was the major reason. Conclusion: Diagnostic tests and monitoring of height, weight, IGF-1 level and thyroid function was properly performed in this setting. However, a number of patients with ISS and Turner's syndrome were under-dosed.